Peer Tutoring and Scaffolding Principle for Inclusive Teaching - Giuliana Nardacchione; Guendalina Peconio (Elementa, 2022)
This paper aims to investigate the theoretical references that the literature offers with respect to the principle of scaffolding and to the methodology of Peer Tutoring from an inclusive perspective. The principle of scaffolding, in fact, has its roots in the first definitions by Vygotskij (1978a) who defines it as the social support provided to the student during the completion of a learning task to solve a problem or achieve a goal. Subsequently, this principle has been declined in an inclusive perspective with respect to classroom management and with respect to new transmedia learning environments. The reference literature was reviewed to highlight the learning outcomes related to the principle of cognitive, metacognitive and emotional scaffolding. In addition, from the point of view of classroom management from an inclusive perspective, a declination that is effective refers to Peer Tutoring. This methodology aims to promote mutual interactions mediated by peers in order to optimize individual functioning and promote the holistic development of the parties involved. Therefore, the Peer Tutoring methodology was highlighted with reference to both the theoretical and practical components of the studies investigated.